Макромоделирование аналоговых интегральных микросхем - Алексенко А. Г. Андрей Геннадьевич; Зуев Б. И. Борис Иванович; Ламекин В. Ф. Владислав Федорович; Романов И. А. Игорь Александрович (Москва, Радио и связь, 1983)
Авт. указаны на обороте тит. листа